7
$\begingroup$

Please how can I solve $$y''(x)+y'(-x)=e^x$$

I tried everything I could I can't even find the complementary solution Any help would be gladly appreciated

Thanks In Advance

$\endgroup$
4
  • 1
    $\begingroup$ Are you familiar with the chain rule? $\endgroup$
    – ty.
    Jun 7 '18 at 19:20
  • $\begingroup$ Yeah I'm familiar with that $\endgroup$ Jun 7 '18 at 19:32
  • $\begingroup$ Could you please show what you tried? Showing your efforts generally helps get an answer here. $\endgroup$
    – User1234
    Jun 7 '18 at 19:34
  • $\begingroup$ In addition that also occasionally helps in reaching the final solution. $\endgroup$
    – User1234
    Jun 7 '18 at 19:35
9
$\begingroup$

Put $u(x) = \frac{y(x) + y(-x)}{2}$ and $v(x) = \frac{y(x) - y(-x)}{2}$. So $y(x) = u(x) + v(x)$ and $y(-x) = u(x) - v(x)$. Then your equation is \begin{equation}\tag{1}u''(x) + v''(x) + v'(x) - u'(x) = e^x.\end{equation} Now you've eliminated the $-x$ from the equation at the cost of adding an extra dependent variable, however you know something about the parity of $u$ and $v$: $u$ is even and $v$ is odd so one possible way to solve is to split the equation into even and odd parts. Since $u$ is even, $u'$ is odd and $u''$ is even. Likewise since $v$ is odd, $v'$ is even and $v''$ is odd. Thus if we can solve the coupled system \begin{equation} \tag{2} u''(x) + v'(x) = \cosh(x) \end{equation} and \begin{equation} \tag{3}v''(x) -u'(x) = \sinh(x) \end{equation} then we'll have solution to $(1)$. Differentiating $(3)$, gives $$u''(x)=v'''(x) - \cosh(x)$$ whence, inserting this into $(2)$ gives $$v'''(x) + v'(x) = 2\cosh(x).$$ This has solution $$v(x) = \sinh(x) + A + B\sin(x) + C\cos(x)$$ and since we know $v$ is odd, we must have $A,C = 0$ so $$\boxed{v(x) = \sinh(x) + B\sin(x),}$$ for some constant $B$. Similarly, differentiating $(2)$ gives $$v''(x) = -u'''(x) + \sinh(x)$$ and inserting this into $(3)$ yields $$u'''(x) + u'(x) = 0$$ which (once we've accounted for the fact that $u$ is even) has solution $$\boxed{u(x) = A + C\cos(x)}$$ for some new constants $A,C$. Then $y(x) = u(x) + v(x)$ yields the solution $$y(x) = \sinh(x) + A + B\sin(x) + C\cos(x).$$ At first this looks like too many linearly independent homogeneous solutions, but if we plug our solution for $u,v$ into $(2)$, we find $$-C\cos(x) + B\cos(x) = 0$$ so $B= C$. Thus our final solution is $$\boxed{y(x) = \sinh(x) + A + B(\sin(x) + \cos(x)),}$$ for arbitrary constants $A,B$.

$\endgroup$
1
  • 2
    $\begingroup$ Thanks so much!! $\endgroup$ Jun 7 '18 at 19:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.